Апелятивні назви осіб у волинських грамотах ХVІ ст.: структурно- семантичні параметри - Павленко, Лариса Петрівна; Pavlenko, Larysa P. (Східноєвропейський національний університет імені Лесі Українки., 2014)
У статті проаналізовано структурно-семантичні особливості номінацій осіб у волинських грамотах ХVІ ст. The article analyzes structural and semantic features of persons’ nominations found in the sixteenth century Volyn charters. The examples of legal writing are of vital importance in the history of literary language whose research is based on the sixteenth century business style material and permits the scientists to study deeper peculiarities of Ukrainian national language of that time. Particular scientific attention should be paid to the written sources that are considered to be the evidence of material and spiritual history of Volyn as a part of the Polish-Lithuanian-Russian state. The region preserved the tradition of the Kyivan Rus legal relationship and developed some elements of European systems at the same time. The sixteenth century Volyn charters illustrate all the semantic richness of persons’ nominations, i.e. common names that reflect political, social, property, family and cultural peculiarities observed in the society of that time.
Appellatives of persons in the sixteenth century Volyn charters: structural and semantic parameters
Keywords: пам’ятки української мови; староукраїнська мова; мовно-стильова специфіка правового письменства; семантична структура; номінативна деривація; живомовні риси; examples of Ukrainian writing; Old Ukrainian; linguistic and stylistic peculiarities of the legal writing; semantic structure; nominative derivation; spoken language features